Amphispirula gen. nov. from the Eocene of southern Moravia (Czech Republic): a new ancestor of the Recent deep-sea squid Spirula?. (1st February 2016) - Fuchs, Dirk; Košťák, Martin
Abstract : A single specimen of an enigmatic coleoid cephalopod from the Eocene of southern Moravia (Czech Republic) represents the oldest record of a spirulid with a markedly, endogastrically coiled phragmocone. Distinctly oblique septa in Amphispirula gen. nov. show similarities to sepiid coleoids, but a ventrally closed siphuncle refers this taxon to the order Spirulida. The existence of a coiled phragmocone-bearing coleoid in the Eocene significantly precedes Miocene records of Spirulirostra – a guard-bearing coleoid, which is suggested to be ancestral to Recent Spirula . A mosaic of morphological features in Amphispirula might point to an older and unknown ancestor of modern Spirula, but more likely represents a new evolutionary lineage within spirulid cehalopods. http://zoobank.org/urn:lsid:zoobank.org:pub:BF5D1CBB-4AD4-4B54-9B45-07E224B24CF3